Updates on Clostridium difficile spore biology. (June 2017) - Gil, Fernando; Lagos-Moraga, Sebastián; Calderón-Romero, Paulina; Pizarro-Guajardo, Marjorie; Paredes-Sabja, Daniel
Abstract: Clostridium difficile is a Gram-positive, anaerobic spore former, and an important nosocomial pathogenic bacterium. C. difficile spores are the morphotype of transmission and recurrence of the disease. The formation of C. difficile spores and their subsequent germination are essential processes during the infection. Recent in vitro and in vivo work has shed light on how spores are formed and the timing of in vivo sporulation in a mouse model. Advances have also been made in our understanding of the machineries involved in spore germination, and how antibiotic-induced dysbiosis affects the metabolism of bile salts and thus impacts C. difficile germination in vivo . Studies have also attempted to identify how C. difficile spores interact with the host's intestinal mucosa. Spore resistance has also been revisited by several groups highlighting the extreme resistance of this morphotype to traditional food processing regimes and disinfectants used in clinical settings. Therefore, the aim of this review is to summarize recent advances on spore formation/germination in vitro and in vivo, spore-host interactions, and spore resistance that contribute to our knowledge of the role of C. difficile spores in the infectious process.